Secretory phospholipase A2 pathway in various types of lung injury in neonates and infants: a multicentre translational study - De Luca, Daniele (BioMed Central, 2011)
BACKGROUND: Secretory phospholipase A2 (sPLA2) is a group of enzymes involved in lung tissue inflammation and surfactant catabolism. sPLA2 plays a role in adults affected by acute lung injury and seems a promising therapeutic target. Preliminary data allow foreseeing the importance of such enzyme in some critical respiratory diseases in neonates and infants, as well. Our study aim is to clarify the role of sPLA2 and its modulators in the pathogenesis and clinical severity of hyaline membrane disease, infection related respiratory failure, meconium aspiration syndrome and acute respiratory distress syndrome. sPLA2 genes will also be sequenced and possible genetic involvement will be analysed. METHODS/DESIGN: Multicentre, international, translational study, including several paediatric and neonatal intensive care units and one coordinating laboratory. Babies affected by the above mentioned conditions will be enrolled: broncho-alveolar lavage fluid, serum and whole blood will be obtained at definite time-points during the disease course. Several clinical, respiratory and outcome data will be recorded. Laboratory researchers who perform the bench part of the study will be blinded to the clinical data. DISCUSSION: This study, thanks to its multicenter design, will clarify the role(s) of sPLA2 and its pathway in these diseases: sPLA2 might be the crossroad between inflammation and surfactant dysfunction. This may represent a crucial target for new anti-inflammatory therapies but also a novel approach to protect surfactant or spare it, improving alveolar stability, lung mechanics and gas exchange.